REUNI : um programa de expansão das universidades federais : o caso da UFMT - Nogueira, Patrícia Simone (2012)
The dissertation discusses the expansion of higher education, focusing on the Federal University of Mato Grosso. The research problem focuses on the deployment and development of the UFMT REUNI - Cuiabá campus, in the period 2007 to 2010. It analyzes the higher education policies (legislation, documents that deal with the REUNI, REUNI of the Decree, the documents UFMT) and conducts interviews with course coordinators, students, senior management of UFMT and representative of the MEC. The basic theoretical and methodological research is based on the historical and dialectical materialism. The results show that the UFMT is not fulfilling the goal agreed upon with the Ministry of Education, through the Agreement targets, as regards the increase in enrollment and enrollment. In the interviews, it is justified that the proposed expansion will not be achieved because the preferred UFMT expand jobs in the distance, at UAB, in addition, it is argued that the proposal was made bolder. Apparently there is no pressure by the MEC to fulfill the goals REUNI, however, research shows signs that are causing overloading of the teaching work and casualization of teaching. In summary, the goals and guidelines REUNI show that the program expands entry, residence permits, even if insufficient, however, does not address the quality of training. It is considered that it is essential to take this moment to expand to be a university in favor of the Brazilian people. For this, the social movements, carried out by civil society organizations are essential. Finally, we conclude that the goals and guidelines REUNI, when implemented, have proven able to change the model of university ruled in teaching, research and extension inseparable.